Effect of heat input on mechanical and microstructural properties of Inconel 625 depositions processed in wire arc additive manufacturing. (October 2021) - Sarathchandra, DT; Davidson, MJ
Inconel 625 alloy resists corrosion, fatigue and wear at elevated temperatures and hence they are used in aerospace, chemical, petrochemical, marine, and other high-temperature applications. In the present study, single beads of Inconel 625 were deposited using the cold metal transfer (CMT) based wire arc deposition process. Seven heat input conditions were used to study the microstructure and mechanical characteristics. Microstructural characterization was done with optical and scanning electron microscopes while microhardness was measured using the Vickers microhardness testing method. It has been observed that the microstructure of the deposited beads consists of a columnar structure with primary dendrites. Also, intermetallic elements like Niobium (Nb), Molybdenum (Mo), and Laves were formed. It was also observed that the percentage of Nb and Mo increases with heat input. The microhardness increases with an increase in heat input and the maximum hardness was found to be 234.7 HV.